ENHANCING NOVICE VOTER PARTICIPATION: STRATEGIES OF THE REGIONAL GENERAL ELECTION COMMISSION FOR THE 2024 JAYAPURA CITY GENERAL ELECTION - Mayor, David E.; Wenggi, Karolina R.S.; Siswanto, Amos; Uang, Dedy Pribadi (Fakultas Politik Pemerintahan, 2024)
This study focuses on the population of Jayapura City and how it has been changing over the years, particularly among the younger generation, which is made up of new voters. This demographic shift will impact political participation, especially in preparation for the 2024 general election. The purpose of this research is to find out and summarize the strategy of the Regional General Election Commission (KPUD) in increasing the participation of novice voters in preparation for the 2024 General Election in Jayapura City, identify supporting factors, and inhibiting factors in carrying out the strategy of the KPUD to increase the participation of novice voters in preparation for the 2024 General Election in Jayapura City. The research method is a descriptive qualitative method with an inductive approach. Data is gathered through observation, interviews, or document reviews. It is then processed by reducing and presenting the data, drawing conclusions, and triangulating the analysis results using the theoretical concepts of Stoner, Freeman, and Gilbert. Jr. The strategy can be defined based on two perspectives: (1) what an organization intends to do and (2) what the organization does. In this study, the authors will discuss it more deeply through further explanation and description. The KPU in Jayapura City has implemented two main strategies to increase the participation of beginner voters. The first strategy involves updating data, while the second focuses on socialization programs. Implementing election preparation is expected to be responsive in data processing and management, especially in the creativity of mapping population data according to specific groups. Furthermore, improving our capabilities, especially in technology, is essential as the digital world advances rapidly. Additionally, the coordination with certain agencies and institutions in updating data, such as the Indonesian National Armed Forces (TNI) and the Indonesian National Police (POLRI), should be reviewed since these are currently inactive.